1993
DOI: 10.1161/01.cir.87.6.1806
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular calcium homeostasis in cardiac myocytes.

Abstract: Calcium homeostasis in cardiac myocytes results from the integrated function of transsarcolemmal Ca2+ influx and efflux pathways modulated by membrane potential and from intracellular Ca2+ uptake and release caused predominantly by SR function. These processes can be importantly altered in different disease states as well as by pharmacological agents, and the resulting changes in systolic and diastolic [Ca2+]i can cause clinically significant alterations in contraction and relaxation of the heart. It may be an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
1
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(138 citation statements)
references
References 80 publications
2
132
1
3
Order By: Relevance
“…In cardiomyocytes, the extrusion and sequestration of free calcium during diastole is dependent on cyclic AMP, is modulated by b-receptors, and is influenced by several ion transport mechanisms including the Na + /H + exchanger. [30][31][32][33][34][35][36] Cardiac b-receptors couple to a G-protein-stimulated adenylcyclase, which in turn stimulates cyclic AMP-dependent regulatory mechanisms. 30,31,33,37 Recent studies in rodent cardiomyocytes revealed that b 2 -receptors couple to G-proteins, which lead to inhibition of cyclic AMP formation downstream.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cardiomyocytes, the extrusion and sequestration of free calcium during diastole is dependent on cyclic AMP, is modulated by b-receptors, and is influenced by several ion transport mechanisms including the Na + /H + exchanger. [30][31][32][33][34][35][36] Cardiac b-receptors couple to a G-protein-stimulated adenylcyclase, which in turn stimulates cyclic AMP-dependent regulatory mechanisms. 30,31,33,37 Recent studies in rodent cardiomyocytes revealed that b 2 -receptors couple to G-proteins, which lead to inhibition of cyclic AMP formation downstream.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33][34][35][36] Cardiac b-receptors couple to a G-protein-stimulated adenylcyclase, which in turn stimulates cyclic AMP-dependent regulatory mechanisms. 30,31,33,37 Recent studies in rodent cardiomyocytes revealed that b 2 -receptors couple to G-proteins, which lead to inhibition of cyclic AMP formation downstream. 38,39 In the ischaemic myocardium, the Na + /H + exchanger, which itself is under the influence of the C825T polymorphism, 3,4 exerts an important modulatory action on cardiac excitation-contraction coupling.…”
Section: Discussionmentioning
confidence: 99%
“…pF, picofarads. exchanger working in the "reverse mode" (17). Even if small, the open probability of the L-type Ca 2ϩ channel at rest is not null as assessed by single channel recording (18).…”
Section: Table I Cell Capacitances and I To Kinetic Parameters After mentioning
confidence: 99%
“…Based on single Hc conductance measurements, it was suggested that opening of only 50 Hc is sufficient to drown the cell with Na + (John et al, 1999b). As a result, Na + overload induces the activation of reverse Na + -Ca ++ exchange and hence promotes intracellular Ca ++ accumulation (Barry & Bridge, 1993;Silverman & Stern, 1994), irreversible cell injury and arrhythmogenic transient inward currents (Tani & Neely, 1989). Altogether, these data endorse the theory of the involvement of the unapposed Hc in ischemic-induced injury and support our hypothesis that inhibition of Hc during ischemia is an important determinant for cardioprotection against ischemia/reperfusion injury.…”
Section: Unapposed Cx43hc Opening In Ischemia/reperfusion Injurymentioning
confidence: 99%